Green matters eco-friendly housing (Victoria, Australia : World Wide Entertaiment, 2010)
"Green Matters is your essential resource for a healthier planet. From the protection of endangered species to the design of ecofriendly homes, Green Matters is a timely look at our planet's most important issues. It is an innovative eco friendly housing project and represents an important element of the British government's push for a 60% reduction in carbon dioxide emissions by the year 2050."
Keywords: Economic development -- Environmental aspects; Environmental health